Epigenetic Plasticity of Fish Pigmentation Under Environmental Stress: A Gene–Environment–Epigenetic Interaction Model - Rabia Tahir; Songlin Cai; Samra; Fozia Afzal; Jinliang Hou; Lingxiao Wang; Ayesha Arif; Mohamed Aboraya; Zhiyi Zhang; Jing Ke; Xin Hou; Jun Wang; et al. (Reviews in Aquaculture, 2026)
Fish pigmentation exhibits remarkable plasticity, enabling rapid and long‐term phenotypic adjustments in response to environmental stressors. We propose a gene–environment–epigenetic (G × E × Ep) interaction model that integrates environmental cues, neuroendocrine signaling, and multilayered epigenetic regulation to explain dynamic pigmentation outcomes. Key mechanisms, including DNA methylation, histone modifications, chromatin remodeling, and non‐coding RNAs, modulate pigment cell differentiation, distribution, and patterning in a context‐dependent manner, while involving α‐melanocyte–stimulating hormone (α‐MSH), melanocyte‐concentrating hormone (MCH), and adrenocorticotropic hormone (ACTH) to relay environmental signals to epigenetic machinery. Emerging genome‐wide and single‐cell epigenomic approaches, together with CRISPR/dCas9‐based epigenome editing, now enable precise mapping and functional validation of these pathways. Adaptive pigmentation enhances ecological fitness, but environmental stress can trigger maladaptive, potentially heritable changes. Importantly, integrating epigenetic knowledge with husbandry practices offers actionable strategies to rescue or stabilize pigmentation under stress, such as environmental modulation, dietary supplementation, and targeted broodstock selection. We identify critical gaps regarding the stability, tissue specificity, and transgenerational inheritance of epigenetic marks and propose a roadmap for applying multilayered epigenomic insights to sustainable aquaculture, ornamental fish management, and climate‐resilient breeding programs.